WACANA KEMADJOEAN DI KELOMPOK ETNIS SUNDA AWAL ABAD 20 - Dhona, Holy Rafika (Universitas Negeri Yogyakarta, 2015)
AbstractKemadjoean (progress) was a key term for all social movement in the early 20th century Dutch East Indies. This article argued that the discourse of progress has no single meaning throughout the Dutch East Indies, but instead, it was practiced differently by people from different cultural communities. This article focuses on how the discourse of progress was negotiated by the Sundanese ethnic group. Using Foucauldian discourse analysis on the texts of Papaes Nonoman Newspaper (1914-1917), this studi found that, besides being interpreted as